Problematika Penyelesaian Perkara Tindak Pidana Politik Uang (Money Politic) dalam Pemilu Legislatif Tahun 2024 - Hanifah Putri Junaedi; Tiara Catur Wulandari; Andini Putri Utami; Intan Wedia Putri; Indah Wedia Putri; Yenny Fitri Z (LPMP Imperium, 2024)
Community service activities aim to provide the community with a proper understanding of the law regarding the practice of money politics. The dissemination was conducted on February 8, 2024, at 2:00 PM local time at a coffee shop in Ibuh Village and on February 13, 2024, at 10:00 AM local time at Mitra Vocational School, West Payakumbuh Subdistrict, Payakumbuh City, West Sumatra Province. The purpose of the dissemination is to raise awareness among the community and first-time voters about the dangers of money politics, its forms, potential sanctions, and the process for reporting such criminal acts. The activity has successfully enhanced the community's understanding of the difficulty in proving money politics cases. Conclusions drawn from the community's perceptions include the majority acknowledging the existence of money politics, recognizing it as an electoral crime, and considering it a cultural norm in Indonesia. Factors influencing these perceptions include individuals' experiences with money politics, their knowledge of such practices, and the political climate during elections. While some respondents, particularly those under 20 years old, view money politics as a normal part of elections, they also realize its detrimental effects on the integrity of elections in Indonesia.